The Winchester guide to keywords and concepts for international students in art, media and design - Makhoul, A. L.; Morley, Simon 1958- (Wiley Blackwell, 2015)
This welcome new resource for international students in art, design, and media provides clear explanations of the terminology and concepts they must master in order to fulfill their academic potential and enrich their professional careers.